(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Cytomegaly virus, having entered a previously uninfected organism, penetrates into cells and begins to replicate actively. The result of replication is the formation of daughter viral particles, which leaving the infected cell are ‘covered’ by the outer shell. In this case, the outer shell of virions is formed with the participation of the cell membrane of the cell damaged by cytomegalovirus. CMV reproduces in lymphocytes, blood monocytes, and persists in lymphoid organs [4,5,6].